2016
DOI: 10.1002/ange.201606972
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Efficiency and Eliminating Degradation in Solid Oxide Electrochemical Cells Using High Oxygen‐Capacity Perovskite

Abstract: Recently,t here have been efforts to use clean and renewable energy because of finite fossil fuels and environmental problems.O wing to the site-specific and weatherdependent characteristics of the renewable energy supply,solid oxide electrolysis cells (SOECs) have received considerable attention to store energy as hydrogen. Conventional SOECs use Ni-YSZ (yttria-stabilized zirconia) and LSM (strontiumdoped lanthanum manganites)-YSZ as electrodes.T hese electrodes,however,suffer from redox-instability and coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…While the water splitting and oxygen reduction occur at the entire electrode surface, the improvement of mass transport is needed to make gas diffusion throughout electrode grains more necessary. The incorporation of the three-dimensional mesh-like PNC Kim et aI., 2016 38 Wang et aI., 2015 39 Chen et aI., 2015 40 Laguna-Bercero et aI., 2016 45 Ishihara et aI., 2016 46 Yang et aI., 2015 47 Peng et aI., 2010 41 Traversa et aI., 2015 42 Xie et aI., 2016 48 He et aI., 2017 49 Ding et aI., 2018 43 Kim et aI., 2018 44 Peng et aI., 2018 50 Liu et aI., 2018 51 Norby et aI., 2019 52 Haile et aI., 2019 53 electrode can make full use of the high porosity and active nanoparticles of nanofibers for superior performance. Our recent result has demonstrated that hydrogen production rate has been greatly improved by this self-architectured ultra porous layered perovskite PBSCF steam electrode 43 , e.g., 0.85 A cm −2 at 1.3 V and 600°C which was increased from regular electrode (0.55 A cm −2 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the water splitting and oxygen reduction occur at the entire electrode surface, the improvement of mass transport is needed to make gas diffusion throughout electrode grains more necessary. The incorporation of the three-dimensional mesh-like PNC Kim et aI., 2016 38 Wang et aI., 2015 39 Chen et aI., 2015 40 Laguna-Bercero et aI., 2016 45 Ishihara et aI., 2016 46 Yang et aI., 2015 47 Peng et aI., 2010 41 Traversa et aI., 2015 42 Xie et aI., 2016 48 He et aI., 2017 49 Ding et aI., 2018 43 Kim et aI., 2018 44 Peng et aI., 2018 50 Liu et aI., 2018 51 Norby et aI., 2019 52 Haile et aI., 2019 53 electrode can make full use of the high porosity and active nanoparticles of nanofibers for superior performance. Our recent result has demonstrated that hydrogen production rate has been greatly improved by this self-architectured ultra porous layered perovskite PBSCF steam electrode 43 , e.g., 0.85 A cm −2 at 1.3 V and 600°C which was increased from regular electrode (0.55 A cm −2 ).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In the last few years, they have attracted attention as fuel electrodes of SOFCs and solid oxide electrolyzer cells due to their high oxygen ionic diffusion rate and high electronic conductivity. [34][35][36][37][38][39][40][41][42][43]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, layered perovskite structures have received considerable attention because of their interesting properties, such as high electrical conductivity, fast surface oxygen exchange and easy oxygen ion diffusion 14 15 16 17 . However, there have been very few reports focussed on exsolution in layered perovskites due to the lack of redox stable layered perovskites.…”
mentioning
confidence: 99%